Alternating Minimization Algorithm for Hybrid Precoding in Millimeter Wave MIMO Systems - Oyedele, Ahmed Oluwaseyi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Millimeter-Wave (mm-Wave) communication has been considered as the leading enabling technology for 5G networks as it provides greater spectrum other than existing cellular bands. It holds a promise to provide an unparalleled 5G cellular network capability increase. Because of the short wavelength of mm-Wave signals, Multiple-Input-Multiple-Output (MIMO) systems through precoding can exploit the use of large-scale antennas to battle rain attenuation and path loss. In contrast to the conventional MIMO systems, mm-Wave MIMO cannot perform precoding entirely at the baseband using digital precoders, as only a limited number of signal mixers and analog-to-digital converters can be supported considering their power consumption. As a cost-effective alternative, a significant attention has recently been given to a hybrid precoding transceiver architecture that combines a digital precoder with an analog precoder. This thesis discusses an Alternating Minimization (AltMin) algorithm focused on manifold optimization for the design of a hybrid precoder, consequently comparing its results to the fully digital precoder design, that nonetheless, has a high complexity. Algorithms of AltMin are further applied to the broadband settings with orthogonal frequency division multiplexing (OFDM) modulation. Simulation results demonstrate that in terms of spectral efficiency, AltMin algorithm can significantly outperform existing algorithms and, more importantly, in some cases it can achieve an optimum performance. Keywords: 5G, alternating minimization, hybrid precoding, low-complexity, manifold optimization, and millimeter-wave

ӦZ: Milimetre-Dalga (mm-Wave) iletişimi, mevcut hücresel bantlardan daha fazla spektrum sağladığı için 5G ağları için önemli bir olanak sağlayan teknoloji olarak düşünülmekte ve eşsiz bir 5G hücresel ağ kabiliyeti artışı sağlama vaadinde bulunmaktadır. Mm-Wave sinyallerinin kısa dalga boyu nedeniyle, Çoklu Giriş-Çoklu Çıkış (MIMO) sistemleri, ön kodlama yoluyla yol kaybı ve yağmur zayıflamasıyla savaşmak için büyük ölçekli antenlerden yararlanmaktadır. Geleneksel MIMO sistemlerinin aksine, mm-Wave MIMO, güç tüketimleri dikkate alındığında yalnızca sınırlı sayıda sinyal karıştırıcısı ve analog-dijital dönüştürücüler desteklenebildiğinden, dijital ön kodlayıcıları kullanarak ana bantta ön kodlamayı tamamen gerçekleştirememektedir. Uygun maliyetli bir alternatif olarak, dijital ön kodlayıcı ile analog ön kodlayıcıyı birleştiren hibrit bir ön kodlama alıcı-verici mimarisine son zamanlarda önem verilmektedir. Bu tezde, hibrid ön kodlayıcıyı tasarlamak için manifold optimizasyonuna dayanan ve yüksek karmaşıklığı olan tamam dijital ön kodlayıcı performansı ile karşılaştırılabilir alternatif bir en aza indirgeme algoritması (AltMin) tartışılmaktadır. AltMin algoritmaları dikey frekans bölmeli çoğullama modülasyonu ile geniş bant ayarına genişletilebilmektedir. Benzetim sonuçları, spektral verimlilik açısından, AltMin algoritmasının mevcut algoritmalardan önemli ölçüde daha iyi performans gösterebileceğini ve daha da önemlisi bazı durumlarda optimum performansa ulaşabileceğini göstermektedir. Anahtar Kelimeler: 5G, alternatif minimizasyon, hibrid ön kodlama, düşük karmaşıklık, manifold optimizasyonu ve milimetre dalga
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2020. Co-Supervisor: Prof. Dr. Ahmet Rızaner and Supervisor: Prof. Dr. Ali Hakan Ulusoy.
Keywords: Electrical and Electronic Engineering; 5G; alternating minimization; hybrid precoding; low-complexity; manifold optimization; and millimeter-wave